Lithospheric delamination and upwelling asthenosphere in the Longmenshan area: insight from teleseismic P-wave tomography - He, Chuansong; Dong, Shuwen; Wang, Yanghua (Scientific reports, 2019)
We apply teleseismic P-wave tomography to reconstruct the velocity structure of the Longmenshan area. Our results show possible large-scale delamination beneath the Songpan-Ganzi and Qiangtang terranes, which induced upwelling asthenosphere. Upwelling asthenosphere might have led to lower crust heating, facilitating eastward extrusion of the Songpan Ganzi terrane resulting in localized deformation and uplift along the Longmenshan orogenic belt. We suggest that the eastward extrusion of the Songpan-Ganzi terrane against the rigid lithospheric root of the Sichuan Basin results in stress accumulation and release, leading to large earthquakes in the Longmenshan area.